The Effect of Adding Fish Oil sunflower seed oil in the produce of yogurt from skim milk on Cholesterol Level of Mice (Mus musculus) - A. Purnama; R. Malaka; A. Ako (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2011)
This study aims to look at the effect of adding fish oil and sunflower seed oil in the produce of yogurt from skim milk as unsaturated fatty acids that can lower blood cholesterol levels are tested on mice (Mus musculus). Materials research is skim milk, lamuru fish oil, sunflower seed oil, starter plain yogurt Lb.delbrueckii subps. bulgaricus, penoptalin 1%, NaOH 0.1 N and experimental animals. Experimental animals used were 27 mice (Mus musculus) which 2-3 month old male and weighing 25-30 gr. This study used a complete randomized design (CRD) factorial 3 x 3 x 3 with the first factor is the percentage of fish oil (0%, 1%, 2%), and the second is the percentage of sunflower seed oil (0%, 1%, 2%). The results showed that the addition of fish oil and sunflower seed oil does not affect percentage of yogurt lactic acid, but very real effect on cholesterol of mice. Reduction of cholesterol levels of mice that is best mice given yogurt with the addition of 2% and 2% fish oil sunflower seed oil.